Functional dichotomy (symmetry - asymmetry) of physical development in men who are engaged in triathlon - Zoya Gorenko; Boris Ocheretko; Antonina Kovelskaya (Kharkiv State Academy of Physical Culture, 2018)
Purpose: explore the dichotomy of the physical development of men who are engaged in triathlon and long-distance running on the highway. Material & Methods: Under the conditions of the exercise test with a hip strength of 94 physically active men, the reaction of the cardio-respiratory system to physical activity was investigated. Body composition was determined using the bioelectric impedance method. For paired signs, the asymmetry coefficient was calculated. (CАS). Results: largest groups of work at the level of maximum oxygen consumption were allocated groups assess the level of fitness of athletes. With an increase in the level of physical performance, individual indicators of the maximum response of the cardiorespiratory system to stress have a multidirectional tendency. The development of the muscles of the lower extremities is characterized by right-sided asymmetry for all groups of athletes. At the same time, the value of CАS increases with the increase in the level of physical performance from the 1st to the 4th group. In amateur with a high level of preparedness, a decrease in this coefficient is observed. Conclusion: most amateur athletes who practice triathlon or long-distance runner on the highway have an asymmetry in their lower limbs. The most pronounced asymmetry has athletes with a performance at the level of maximum oxygen consumption of 4,0-4,5 W∙kg-1. In the first to fourth groups, an increase in the asymmetry of the lower extremities is observed, whereas in the group with high performance (4,6-5,5 W∙kg-1), the asymmetry decreases, which may be a necessary condition for achieving high results.